Peran Guru Madrasah dalam Mengembangkan Growth Mindset Islami untuk Meningkatkan Ketekunan Belajar Siswa - Alvina Zein; Susanti Susanti; Fakhriyatul Husna; Yulia Yulia; Masyitah Masyitah (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2025)
In Islamic education, the role of madrasah teachers extends beyond delivering material; they are also responsible for shaping students' mindsets and Islamic character. One of the key emerging approaches is the Islamic-oriented growth mindset, which emphasizes the belief that individuals’ abilities can be developed through effort, proper strategy, and Islamic values.. However, there is still a limited number of studies that specifically examine how teachers contribute to developing a growth mindset learning style that affects students' persistence in learning. This study aims to systematically review the literature discussing the connection between teachers' roles, growth mindset, and learning perseverance. A descriptive qualitative approach was used through a literature review method. The results indicate that teachers play a crucial role in creating a learning environment that supports the learning process, provides constructive feedback, and encourages students to face challenges. These factors contribute to the development of students' perseverance, which is essential for academic success. The study concludes that strengthening the teacher's role in fostering a growth mindset is a key strategy in building resilient and persistent learners. This mindset is also supported by Islamic values such as effort (ikhtiar), perseverance (sabr), and consistency (istikamah) which reinforce students’ resilience in learning.